Donor Selection for Allogenic Hemopoietic Stem Cell Transplantation: Clinical and Ethical Considerations. (7th June 2017) - Riezzo, Irene; Pascale, Natascha; La Russa, Raffaele; Liso, Arcangelo; Salerno, Monica; Turillazzi, Emanuela
Abstract : Allogenic hematopoietic progenitor cell transplantation (allo-HSCT) is an established treatment for many diseases. Stem cells may be obtained from different sources: mobilized peripheral blood stem cells, bone marrow, and umbilical cord blood. The progress in transplantation procedures, the establishment of experienced transplant centres, and the creation of unrelated adult donor registries and cord blood banks gave those without an human leucocyte antigen- (HLA-) identical sibling donor the opportunity to find a donor and cord blood units worldwide. HSCT imposes operative cautions so that the entire donation/transplantation procedure is safe for both donors and recipients; it carries with it significant clinical, moral, and ethical concerns, mostly when donors are minors. The following points have been stressed: the donation should be excluded when excessive risks for the donor are reasonable, donors must receive an accurate information regarding eventual adverse events and health burden for the donors themselves, a valid consent is required, and the recipient's risks must be outweighed by the expected benefits. The issue of conflict of interest, when the same physician has the responsibility for both donor selection and recipient care, is highlighted as well as the need of an adequate insurance protection for all the parties involved.